The principle of VAT neutrality: content and relationship with tax legislation - A. D. Shelkunov (Правоприменение, 2022)
The subject. The principle of VAT neutrality is actual for Russia as VAT is one of the taxes levied in Russia. The principle of VAT neutrality has been upheld by the Russian Supreme Court. Therefore, the subject of the research is the definition of this principle as well as the problems of its relationship with the Russian tax law.Purpose of the study. The article considers the principle of value added tax neutrality as an independent principle of tax law, analyzes its content and regulatory role as independent means of legal regulation. Dealing with foreign doctrine regarding to the referred principle, the article shows the problems of its implementation in Russia and includes suggestions re its harmonization with the Russian tax legislation.Methodology. The author uses the formally legal interpretation of the legal provisions, comparative analysis of Russian and European literature as regards the nature and neutrality principle of VAT as well as the systemic analysis.The main results. The author has formulated the definition of the principle of VAT neutrality and determined the elements of the referred principle. Each element of the principle has been described. The author divided the content of the referred principle on property, legal, economic and competitive elements. However, all these elements should be considered systemically as VAT is supposed to be neutral for businesses in terms of each sphere of their business activity. The author concluded that VAT is the tax on consumption and the burden of this tax should be transferred on final consumers. Taxable persons are only public agents to collect VAT after taxable transactions with final consumers. Therefore, there should be no obstacles as regards the right to deduct input VAT as well as any rules distinguishing the tax burden for similar taxable transactions. Also, due to the deduction mechanism the burden of VAT in the same price of goods (services, work) should be equal and does not depend on the quantity of transactions to be previous to the sale to any final consumer.  As regards the Russian tax legislation, the author identified the rules infringing the principle of VAT neutrality. Thus, the author has concluded that the Russian tax rules establishing strict documentary requirements to the right to deduct input VAT and limiting this right for foreign businesses contradict the principle of VAT neutrality. Also, the rules of the Russian Tax Code which stipulate the exemptions for the transactions between taxable persons and the different tax rates for the similar transactions as well as exclude the persons of the special tax schemes from VAT regime are not in line with referred principle.Conclusions. According to the results of the study, the author has formulated the suggestions regarding to the amendments to the tax legislation in order to correct the revealed mismatches between the provisions of the chapter 21 of the Russian Tax Code and the principle of VAT neutrality. It is proposed to reduce the requirements to the right to deduct as well as exclude the current limitation of this right for foreign businesses, the different tax rates for the similar transactions and the exemptions for the transactions between taxable persons. In addition, the author has suggested to entitle the persons of the special tax schemes to refuse their excluding from VAT regime.